Separation membrane and method for producing same

By forming layered crystals on the side of the dense layer of the poly(4-methyl-1-pentene) separation membrane and controlling its area ratio, the shortcomings of the separation membrane in the prior art in terms of solvent resistance and breathability are solved. High solvent resistance and sufficient breathability are achieved.

CN119486800APending Publication Date: 2025-02-18TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380051368.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the separation membrane made of poly(4-methyl-1-pentene) has shortcomings in solvent resistance and breathability, and it is difficult to achieve high solvent resistance and sufficient breathability at the same time.

Method used

By forming a dense layer on at least one surface layer of the separation membrane and forming layered crystals on the surface on one side of the dense layer, the area ratio of the layered crystals is controlled to be 5 to 50% to achieve high solvent resistance and breathability.

Benefits of technology

The high solvent resistance and breathability of the poly(4-methyl-1-pentene) separation membrane is achieved, and the overall performance of the membrane is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222658650000131
    Figure BDA0005222658650000131
  • Figure BDA0005222658650000132
    Figure BDA0005222658650000132
  • Figure BDA0005222658650000241
    Figure BDA0005222658650000241
Patent Text Reader

Abstract

A separation membrane having poly (4-methyl-1-pentene) as the main component and having a dense layer on at least one surface layer, the surface (1) on the side having the dense layer being 5-50% in area proportion of layered crystals. According to the present invention, a separation membrane having high solvent resistance and gas permeability is provided using poly (4-methyl-1-pentene).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a separation membrane and a method for producing the same. Background Art

[0002] As a degassing method for removing dissolved gas from a liquid or a gas exchange method for exchanging dissolved gas in a liquid with a gas component in a gas phase, there is a method using a hollow fiber membrane. For the hollow fiber membrane used in these applications, solvent resistance and high air permeability are required for the treated liquid, so poly (4-methyl-1-pentene) with excellent characteristics is sometimes used as a membrane material. Among them, a membrane having a dense layer on at least one surface can suppress the infiltration of a solvent into the interior of the membrane by contacting the side having a dense layer with a solvent, so it is preferred from the viewpoint of improving solvent resistance.

[0003] Various methods have been proposed so far to obtain a breathable membrane having high air permeability by using poly(4-methyl-1-pentene) as a membrane material. For example, Patent Document 1 discloses a wet method using a polyolefin polymer. Specifically, a polymer solution obtained by dissolving a polyolefin polymer in a good solvent is extruded from a spinneret at a temperature higher than the melting point of the polyolefin resin, and the polymer solution is brought into contact with a cooling solvent to form a membrane having an asymmetric structure on one surface by heat-induced phase separation, wherein the asymmetric structure has a dense layer.

[0004] Patent document 2 discloses a method for manufacturing a hollow fiber membrane using a melting method. Specifically, a polyolefin resin is extruded from a spinneret at a temperature above the melting point, cooled and solidified, and then stretched, thereby partially cracking to open holes inside, forming a hollow fiber membrane with a structure having a dense surface layer and a porous interior.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Publication No. 2002-535114

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 7-116483 Summary of the invention

[0009] Problems to be solved by the invention

[0010] According to the knowledge of the present inventors, it is difficult to achieve high solvent resistance in the separation membrane of Patent Document 1. In addition, according to the knowledge of the present inventors, although the separation membrane obtained in Patent Document 2 has high strength, it has insufficient porosity and does not have sufficient air permeability, and further, insufficient solvent resistance. Thus, the membrane containing poly(4-methyl-1-pentene) as the main component in the prior art cannot fully exhibit solvent resistance.

[0011] In view of the above problems of the prior art, the present inventors aimed to provide a separation membrane having particularly high solvent resistance using poly(4-methyl-1-pentene).

[0012] Means for solving problems

[0013] In order to solve the above-mentioned problems, the present inventors conducted intensive research and found that even a membrane with poly(4-methyl-1-pentene) as the main component, a membrane having a surface on the dense layer side, i.e., the so-called liquid-contacting membrane surface formed by the aggregation of layered crystals, has high solvent resistance compared with a membrane without layered growth, thereby completing the present invention.

[0014] That is, the separation membrane of the present invention contains poly(4-methyl-1-pentene) as a main component and has a dense layer in at least one surface layer, and the area ratio of lamellar crystals in the surface (1) having the dense layer is 5 to 50%.

[0015] Effects of the Invention

[0016] According to the present invention, poly(4-methyl-1-pentene) is used to provide a separation membrane having high solvent resistance and gas permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 : Figure 1 This is an example of an image obtained by photographing a cross section cut in the thickness direction of the separation membrane using an SEM at a magnification of 10,000 times.

[0018] Figure 2 : Figure 2 Yes Figure 1 The image is binarized and the noise is removed.

[0019] Figure 3 : Figure 3 is from Figure 2 The outlines of voids larger than 10 nm are extracted from the image to show a map of the dense layer thickness.

[0020] Figure 4 : Figure 4 This is an example of an image obtained by photographing the surface of the separation membrane using a SEM at a magnification of 60,000 times.

[0021] Figure 5 : Figure 5 This is an example of an image obtained by cutting an image obtained by photographing the surface of the separation membrane using an SEM at a magnification of 60,000 times into an image of 512×512 pixels.

[0022] Figure 6 : Figure 6 Yes Figure 5 Image obtained by Fourier transform.

[0023] Figure 7 : Figure 7 It is shown Figure 6 The figure shows the range from -90° to 90° with a length of 50 pixels from the center of the image.

[0024] Figure 8 : Figure 8 So from Figure 6 The object is a range of 50 pixels and 4° from the center point of the image, and the average intensity of the range is calculated. The horizontal direction of the image is set to 0° and the operation is performed sequentially in the range of -90° to 90°. The horizontal axis is the angle from the center point, and the vertical axis is the average intensity at each angle to create a graph. DETAILED DESCRIPTION

[0025] The separation membrane of the present invention has poly(4-methyl-1-pentene) as a main component and has a dense layer in at least one surface layer, and the area ratio of the lamellar crystals in the surface (1) on the side having the dense layer is 5 to 50%. In this specification, the ratio (percentage, part, etc.) based on mass is the same as the ratio (percentage, part, etc.) based on weight.

[0026] (Resin composition constituting separation membrane)

[0027] The resin composition constituting the separation membrane of the present invention contains poly(4-methyl-1-pentene) (hereinafter referred to as "PMP") as shown below (1) as a main component. In addition to (1) PMP, it may contain the following components (2) to (6).

[0028] (1) Poly(4-methyl-1-pentene) (hereinafter referred to as "PMP")

[0029] The separation membrane of the present invention needs to contain PMP as a main component. The main component here refers to the component with the largest mass content among all the components constituting the separation membrane.

[0030] PMP is a polymer having repeating units derived from 4-methyl-1-pentene. PMP may be a homopolymer of 4-methyl-1-pentene, or a copolymer with a monomer copolymerizable with 4-methyl-1-pentene other than 4-methyl-1-pentene. Specific examples of monomers copolymerizable with 4-methyl-1-pentene include olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene (hereinafter referred to as "olefins having 2 to 20 carbon atoms"). In the case of a copolymer, the ratio of the repeating units derived from 4-methyl-1-pentene to the other repeating units in the copolymer is preferably in the range of 4-methyl-1-pentene / other repeating units = 100 / 0 to 50 / 50 in terms of molar ratio, more preferably 100 / 0 to 85 / 15, and even more preferably 100 / 0 to 90 / 10.

[0031] Examples of the olefin having 2 to 20 carbon atoms to be copolymerized with 4-methyl-1-pentene include ethylene, propylene, 1-butene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene and 1-eicosene.

[0032] The olefin having 2 to 20 carbon atoms to be copolymerized with 4-methyl-1-pentene may be one kind or a combination of two or more kinds.

[0033] The density of the PMP used in the present invention is preferably 825 to 840 (kg / m 3 ), more preferably 830 to 835 (kg / m 3 When the density is less than the above range, the mechanical strength of the separation membrane may be reduced, defects may occur, etc. On the other hand, if the density is greater than the above range, the air permeability of the separation membrane tends to be reduced.

[0034] The melt flow rate (MFR) of PMP measured at 260°C and 5 kg load is not particularly specified as long as it is easily mixed with the plasticizer (B) described later and can be co-extruded, but is preferably 1 to 200 g / 10 min, more preferably 5 to 30 g / 10 min. If the MFR is within the above range, it is easy to extrude into a relatively uniform film thickness.

[0035] PMP can be directly produced by polymerizing olefins, or can be produced by thermally decomposing high molecular weight 4-methyl-1-pentene polymers. In addition, 4-methyl-1-pentene polymers can be purified by solvent fractionation using differences in solubility relative to solvents, or molecular distillation using differences in boiling points for separation and preparation.

[0036] PMP may be a commercially available polymer such as "TPX (registered trademark)" manufactured by Mitsui Chemicals, Inc., in addition to the products manufactured as described above.

[0037] The content of PMP in the separation membrane is preferably 70 to 100 mass %, more preferably 80 to 100 mass %, and even more preferably 90 to 100 mass %, when all components of the separation membrane are 100 mass %. When the content of PMP in the separation membrane is 70 mass % or more, air permeability becomes sufficient.

[0038] (2) Plasticizer for PMP

[0039] The resin composition constituting the separation membrane of the present invention may contain a plasticizer for PMP. From the viewpoint of improving permeability, the content of the plasticizer in the separation membrane is preferably 1000 ppm (mass basis), more preferably 500 ppm (mass basis) or less, and particularly preferably 100 ppm (mass basis) or less.

[0040] The plasticizer for PMP is not particularly limited as long as it is a compound that can thermally plasticize PMP. The plasticizer for PMP may be used not only as a single plasticizer but also as a combination of two or more plasticizers.

[0041] Examples of plasticizers for PMP include palm kernel oil, dibutyl phthalate, dioctyl phthalate, benzyl ether, coconut oil, or mixtures thereof. Among them, compounds selected from dibutyl phthalate and benzyl ether are preferably used from the viewpoint of compatibility and wire drawing properties.

[0042] The plasticizer of PMP is preferably dissolved out from the separation membrane after the separation membrane is formed.

[0043] (3) Additives

[0044] The resin composition constituting the separation membrane of the present invention may further contain additives other than those described in (2) within a range not impairing the effects of the present invention.

[0045] Examples of the additives include resins such as cellulose ether, polyacrylonitrile, polyolefin, polyvinyl compound, polycarbonate, poly(meth)acrylate, polysulfone or polyethersulfone, organic lubricant, crystal nucleating agent, organic particles, inorganic particles, end-capping agent, chain extender, ultraviolet absorber, infrared absorber, anti-coloring agent, matting agent, antibacterial agent, antistatic agent, deodorant, flame retardant, weathering agent, antistatic agent, antioxidant, ion exchanger, defoaming agent, coloring pigment, fluorescent brightener or dye, etc.

[0046] (Shape of separation membrane)

[0047] The separation membrane of the present invention preferably has a hollow fiber shape (hereinafter referred to as a "hollow fiber membrane"). Hollow fiber membranes are preferred because they can be efficiently filled into a module and can increase the effective membrane area per unit volume of the module.

[0048] The shape of the separation membrane in the present invention, that is, the thickness of the separation membrane, the outer diameter and inner diameter when the separation membrane is a hollow fiber membrane, and the hollowness ratio can be observed by, for example, applying stress to the separation membrane that has been sufficiently cooled in liquid nitrogen, cutting it in the thickness direction of the membrane, and observing the obtained cross section (hereinafter referred to as "diameter cross section") using an optical microscope or a scanning electron microscope (SEM). The specific method is described in detail in the Examples.

[0049] From the viewpoint of taking both permeability and membrane strength into consideration, the thickness of the separation membrane is preferably 10 to 500 μm. In addition, the thickness is more preferably 30 μm or more, and further preferably 50 μm or more. The thickness is more preferably 200 μm or less, further preferably 150 μm or less, and particularly preferably 100 μm or less.

[0050] From the viewpoint of taking into account both the effective membrane area and membrane strength when filling the module, the outer diameter of the hollow fiber membrane is preferably 50 to 2500 μm. The outer diameter of the hollow fiber membrane is more preferably 100 μm or more, further preferably 200 μm or more, and particularly preferably 300 μm or more. In addition, the outer diameter is more preferably 1000 μm or less, further preferably 500 μm or less, and particularly preferably 450 μm or less.

[0051] In addition, from the relationship between the pressure loss of the fluid flowing in the hollow part and the buckling pressure (seat buckling pressure), the inner diameter of the hollow fiber membrane is preferably 20 to 1000 μm. The inner diameter of the hollow fiber membrane is more preferably 50 μm or more, further preferably 100 μm or more, and particularly preferably 150 μm or more. In addition, the inner diameter is more preferably 500 or less, further preferably 300 μm or less, and particularly preferably 250 μm or less.

[0052] In addition, from the relationship between the pressure loss of the fluid flowing in the hollow part and the buckling pressure, the hollowness of the hollow fiber membrane is preferably 15 to 70%. The hollowness is more preferably 20% or more, and further preferably 25% or more. In addition, the hollowness is more preferably 60% or less, further preferably 50% or less, and particularly preferably 40% or less.

[0053] Figure 1 An example of an image obtained by taking a cross section of a separation membrane cut along the thickness direction using a SEM at a magnification of 10,000 times is shown. Figure 1 The image is de-noised and binarized. Figure 2 , and further, from Figure 2 The outline of the voids larger than 10 nm is extracted from the image and the thickness of the dense layer is shown in Figure 3 .

[0054] There is no particular limitation on the method for making the outer diameter, inner diameter and hollow ratio of the hollow fibers in the hollow fiber membrane within the above ranges. For example, the method can be adjusted by appropriately changing the draft ratio, which can be calculated by the shape of the discharge hole of the spinning spinneret for manufacturing the hollow fibers or the winding speed / discharge speed.

[0055] The separation membrane of the present embodiment has a dense layer in at least one surface layer. When the separation membrane is a hollow fiber membrane, the dense layer may be located on the outer surface side, may be located on the inner surface side, or may be located on both the outer surface and the inner surface. Here, the dense layer refers to the portion until the first time a hole with a diameter exceeding 10 nm is reached when a straight line perpendicular to the surface is drawn from any point on the surface 1 of the separation membrane to the other surface side when observing the cross section cut along the thickness direction of the separation membrane using SEM at a magnification of 10,000 times. That is, in the separation membrane, the portion of the surface layer that does not have a hole with a diameter exceeding 10 nm is the dense layer. The layer other than the dense layer in the separation membrane is called the support layer. That is, the support layer is the portion of the separation membrane that has a hole with a diameter exceeding 10 nm.

[0056] For example, stress is applied to the separation membrane fully cooled in liquid nitrogen (using a razor or a slicer or a wide ion beam as needed), and the cross section (hereinafter, shown as "cross section") perpendicular to the length direction of the separation membrane and parallel to the film thickness direction or the cross section (hereinafter, shown as "longitudinal section") parallel to the length direction of the separation membrane and parallel to the film thickness direction is exposed. The cross section is observed using SEM, and after the resulting image is binarized in the image analysis software "ImageJ", only holes greater than 10nm are extracted, thereby the dense layer and the support layer can be distinguished. It should be noted that the cross section of the hollow fiber membrane has the same meaning as the diameter section. In addition, the length direction of the hollow fiber membrane refers to the direction perpendicular to the width direction of the hollow fiber membrane. The width direction of the hollow fiber membrane refers to the direction parallel to the diameter direction of the hollow fiber membrane, and the width direction can be in other words a direction parallel to the hollow surface, i.e., the in-plane direction of the hollow surface. Therefore, the length direction of the hollow fiber membrane can be in other words a direction perpendicular to the hollow surface. The dense layer thickness 2 refers to the length from any point on the outer surface 1 of the separation membrane to the inner surface when a straight line perpendicular to the outer surface is drawn from the inner surface to the first pore with a diameter exceeding 10 nm in the SEM image. The specific measurement method is described in detail in the Examples.

[0057] The thickness of the dense layer is preferably 0.1 to 0.8 μm. When the thickness of the dense layer is 0.1 μm or more, the leakage resistance becomes good, and when the thickness of the dense layer is 0.8 μm or less, the permeability becomes good.

[0058] The thickness of the dense layer is more preferably 0.1 to 0.6 μm. Furthermore, the thickness of the dense layer is further preferably 0.1 to 0.5 μm, and particularly preferably 0.1 to 0.4 μm.

[0059] In addition, the separation membrane of the present embodiment has a plurality of voids in the support layer. The voids in the support layer refer to recesses with a diameter greater than 10 nm when the support layer in the cross section or longitudinal section of the separation membrane is observed using SEM. When the support layer in the cross section or longitudinal section is observed using SEM at a magnification of 2,000 times, the support layer preferably has 10 or more voids per field of view (vertical: about 45 μm, horizontal: about 63 μm). On the other hand, when the separation membrane of the present embodiment is observed in the cross section or longitudinal section using SEM at a magnification of 2,000 times, it is preferred that the number of voids greater than 10 μm per field of view in the support layer is 3 or less. The strength of the separation membrane becomes good by having a void greater than 10 μm in the support layer being 3 or less. The voids greater than 10 μm in the support layer can be measured by observing the cross section or longitudinal section of the separation membrane using SEM at a magnification of 2,000 times, and extracting only pores with an average diameter greater than 10 μm after binarization of the obtained image in the image analysis software "ImageJ". The number of voids larger than 10 μm in the support layer is more preferably 2 or less, further preferably 1 or less, and particularly preferably 0. The method for measuring voids larger than 10 μm in the support layer is described in detail in Examples.

[0060] The separation membrane of the present embodiment preferably has an average pore size of 100 to 1000 nm in the support layer. The average pore size of the support layer can be measured by observing the cross section or longitudinal section of the separation membrane at a magnification of 10,000 times using SEM, and binarizing the obtained image in the image analysis software "ImageJ" to extract only the pores with an average diameter greater than 10 nm. When the average pore size of the support layer is 100 nm or more, the permeability of the separation membrane becomes good, and when it is 1000 nm or less, the strength of the separation membrane becomes good. The average pore size of the support layer is preferably 100 to 800 nm, more preferably 100 to 600 nm, further preferably 100 to 570 nm, and particularly preferably 100 to 500 nm. The method for determining the average pore size of the support layer is described in detail in the examples.

[0061] (Porosity)

[0062] The separation membrane of the present invention preferably has a porosity of 30% or more and 70% or less. When the porosity is 30% or more, the permeability of the separation membrane becomes good, and when it is 70% or less, the membrane strength becomes good. The porosity is preferably 40% or more and 65% or less, more preferably 45% or more and 60% or less, and particularly preferably 53% or more and 60% or less. In order to obtain a porosity in this range, it is preferred to use a structure formation of heat-induced phase separation described later. It should be noted that the porosity referred to here refers to the porosity of the separation membrane as a whole. The specific method for measuring the porosity is described in detail in the examples.

[0063] (Layered crystals on the surface)

[0064] The separation membrane of the present invention is important in that the area ratio of the layered crystals in the surface (1) of the side having the dense layer is 5 to 50%. It is preferred that the area ratio of the layered crystals in the surface (1) is 5% or more in order to obtain high solvent resistance, and that the area ratio is 50% or less in order to obtain good permeability.

[0065] In the present invention, the surface (1) having a dense layer side refers to the surface on which the dense layer side is observed by cross-sectional SEM observation. The observation of the dense layer based on cross-sectional SEM observation is as described above. The layered crystals in the surface (1) having a dense layer side refer to the portions observed as striped convex portions, i.e., striped bright portions, in the image of the surface (1) observed at a magnification of 60,000 times using SEM. When the separation membrane is in the shape of a hollow fiber, the surface (1) having a dense layer side is preferably the outer surface. It should be noted that an example of an image obtained by photographing the surface of the separation membrane at a magnification of 60,000 times using SEM is shown in Figure 4 .

[0066] The area ratio of the lamellar crystals in the surface (1) is preferably 20 to 50%, more preferably 23 to 46%, further preferably 23 to 45%, and particularly preferably 30 to 40%.

[0067] In addition, the period of the lamellar crystals in the surface (1) is preferably 10 to 80 nm. When the period of the lamellar crystals is 10 nm or more, the solvent resistance of the separation membrane becomes good, and when it is 80 nm or less, the permeability of the separation membrane becomes good. The period of the lamellar crystals is more preferably 20 to 50 nm, further preferably 25 to 45 nm, and particularly preferably 30 to 45 nm. The specific method for measuring the period of the lamellar crystals is described in the examples.

[0068] (Presence or absence of orientation of layered crystals on the surface, orientation direction of layered crystals)

[0069] In the separation membrane of the present invention, the lamellar crystal orientation on the surface is preferred. By orienting the lamellar crystals on the surface, the gaps between the lamellar crystals, that is, the amorphous part, become less, and the solvent resistance of the separation membrane is excellent, which is preferred from this point of view. The presence or absence of orientation of the lamellar crystals can be confirmed by the method described later.

[0070] In the present invention, the orientation direction of the layered crystal refers to the angle formed by the length direction of the layered crystal and the length direction of the separation membrane, which can be obtained from the surface SEM image of the separation membrane. The orientation direction of the layered crystal is preferably 60 to 120°, more preferably 65 to 115°, and further preferably 70 to 110°.

[0071] The method for determining the orientation direction of the layered crystal is described in detail below. Figure 5As shown, a surface SEM image obtained by taking a photo at 60,000 times in a manner that the length direction 3 of the separation membrane becomes a horizontal direction is used. The surface SEM image is Fourier transformed to obtain a circular image. In the sample where the layered crystal is not oriented, there is no large change in intensity along the circle, but in the sample where the layered crystal is oriented, the intensity distribution on the circle is biased. Therefore, the orientation direction can be obtained based on the intensity distribution. More specifically, the SEM image is cut into 512×512 pixels, and after Fourier transformation, the horizontal direction of the Fourier transform image is set to 0°. For the range of -90° to 90°, the range of 50 pixels and 4° in length from the center point of the Fourier transform image is used as the object, and scanning is performed sequentially. Calculate the average intensity of the scanning range for each scan. By performing this operation every 4° from -90° to 90°, a graph is made in which the scanning angle is plotted on the horizontal axis and each average intensity is plotted on the vertical axis. The angle obtained by adding 90° to the angle showing the maximum value in the figure is set as the orientation direction of the layered crystal.

[0072] An example of an image obtained by cutting an image of the surface of the separation membrane using an SEM at a magnification of 60,000 times into 512×512 pixels is shown in FIG. Figure 5 ,Will Figure 5 The image obtained by Fourier transform of the image is shown in Figure 6 . Figure 7 Shown in Figure 6 The range of -90° to 90° is 50 pixels long from the center of the image. Figure 6 The image is scanned from -90° to 90° as described above, and the result is plotted to create a diagram. Figure 8 The angle obtained by adding 90° to the maximum angle shown in this figure is the orientation direction of the lamellar crystal.

[0073] It should be noted that the presence or absence of orientation of the layered crystals can be confirmed by the following method. As described above, in a graph in which the scanned angle is plotted on the horizontal axis and the average intensity at each angle is plotted on the vertical axis, when the minimum and maximum values ​​of the average intensity do not differ by more than 5%, that is, when the value of 100×(MAX-MIN) / MAX when the maximum value of the average intensity is MAX and the minimum value is MIN is less than 5, it can be considered that the layered crystals are not oriented.

[0074] (Crystallinity of outer surface)

[0075] The separation membrane of the present invention preferably has a crystallinity of 5 to 30% in the surface (1). When the crystallinity of the surface (1) is 5% or more, the solvent resistance of the separation membrane becomes good, and when it is 30% or less, the permeability of the separation membrane becomes good. The crystallinity in the surface (1) refers to the value determined by infrared spectroscopy (hereinafter sometimes referred to as "IR"), and the specific measurement method is explained by the examples. The crystallinity in the surface (1) is more preferably 15 to 30%, further preferably 17 to 30%, and particularly preferably 20 to 28%.

[0076] (Breathability)

[0077] The separation membrane of the present invention preferably has a N2 permeability of 5 GPU or more at a differential pressure of 100 kPa and 37° C. The N2 permeability is more preferably 10 GPU or more, further preferably 40 GPU or more, further more preferably 50 GPU or more, and particularly preferably 60 GPU or more. The calculation method is described in detail by the examples.

[0078] (CO2 / N2 selectivity)

[0079] Generally, the permeability in a polymer membrane depends on the pore size in the membrane. In the dense layer, the gas permeates by a dissolution-diffusion mechanism. At this time, the separation coefficient α, which represents the ratio of the permeability coefficient P of two gases or the permeation flow rate Q of the gas, depends only on the polymer material forming the dense layer, and does not depend on the thickness of the dense layer. When the gas separation coefficient of CO2 and N2 is set to α(CO2 / N2), the permeability coefficients of CO2 and N2 are set to P(CO2) and P(N2), respectively, and the permeation flow rates of CO2 and N2 are set to Q(CO2) / Q(N2), respectively, the gas separation coefficient α(CO2 / N2) can be expressed as P(CO2) / P(N2) or Q(CO2) / Q(N2). In commonly used polymers, at least one or more α(CO2 / N2) values ​​are generated.

[0080] On the other hand, in the support layer, the gas mainly permeates by "Knudsen diffusion". At this time, the gas separation coefficient α is obtained by the square root of the ratio of the molecular weights of the gases. Therefore, α(CO2 / N2) is √28 / 44=0.80.

[0081] The separation membrane of the present invention has a very long leakage time due to the presence of a dense layer. On the other hand, the separation membrane without a dense layer has a short leakage time. As described above, the permeation of gas is carried out by a dissolution-diffusion mechanism in the dense layer and by Knudsen diffusion in the support layer. That is, by measuring α(CO2 / N2), the density of the separation membrane caused by the presence of the dense layer can be evaluated.

[0082] When the gas separation coefficient α(CO2 / N2) is less than 1, the membrane has a large number of pores or defects in the dense layer. When there are a large number of pores or defects in the dense layer, premature liquid leakage or plasma leakage occurs. This separation membrane is not suitable for long-term use. Similarly, this separation membrane cannot be used in the field of gas separation. In contrast, when the gas separation coefficient α(CO2 / N2) is greater than 1.0, this separation membrane has low leakage. Therefore, the gas separation coefficient α(CO2 / N2) of the separation membrane of the present invention is preferably greater than 1.0, more preferably greater than 2.0, further preferably greater than 3.0, and particularly preferably greater than 4.0.

[0083] (Change rate of permeability before and after chloroform immersion)

[0084] When the N2 permeability of the separation membrane under a differential pressure of 100 kPa is X, and the N2 permeability of the same separation membrane under a differential pressure of 100 kPa measured in the same manner after immersion in chloroform for 5 seconds is Y, the value of the N2 permeability change rate Y / X is preferably 0.3 to 1.2. When the value of the N2 permeability change rate Y / X is 0.3 to 1.2, the solvent resistance becomes good. The specific method for measuring the N2 permeability is described by the examples. The value of the N2 permeability change rate Y / X is more preferably 0.45 to 1.2, further preferably 0.5 to 1.2, and particularly preferably 0.7 to 1.2.

[0085] (Method for producing separation membrane)

[0086] The method for producing a separation membrane of the present invention comprises the following steps (1) to (2):

[0087] (1) a preparation step of melt-kneading a mixture containing 10 to 50% by mass of PMP and 50 to 90% by mass of a plasticizer to obtain a resin composition;

[0088] (2) Molding step: The resin composition is discharged from a discharge spinneret having a gap of 0.05 to 0.3 mm, passed through an air path having a distance of 30 to 80 mm from the spinneret plane to the solvent plane, and then wound to obtain a resin molded product.

[0089] Next, the method for producing the separation membrane of the present invention will be specifically described, taking the case where the separation membrane is a hollow fiber membrane as an example.

[0090] (Preparation process)

[0091] In the preparation process of obtaining a resin composition for manufacturing the separation membrane of the present invention, a mixture containing 10 to 50% by mass of PMP and 50 to 90% by mass of a plasticizer is melt-kneaded. When the content of PMP is 10% by mass or more, the membrane strength of the separation membrane becomes good. On the other hand, when the content of PMP is 50% by mass or less, the permeability of the separation membrane becomes good. In addition, when the content of the plasticizer is 90% by mass or less, the membrane strength of the separation membrane becomes good. In addition, when the content of the plasticizer is 50% by mass or more, the permeability of the separation membrane becomes good. The mixture preferably contains 15 to 50% by mass of PMP and 50 to 85% by mass of a plasticizer, more preferably contains 20 to 45% by mass of PMP and 55 to 80% by mass of a plasticizer, and particularly preferably contains 25 to 40% by mass of PMP and 60 to 75% by mass of a plasticizer.

[0092] For the apparatus used in the melt kneading of the mixture, a kneader, a roll mill, a Banbury mixer, or a mixer such as a single-shaft or twin-shaft extruder can be used. Among them, from the viewpoint of making the uniform dispersibility of the plasticizer good, a twin-shaft extruder is preferably used, and from the viewpoint of being able to remove volatile substances such as moisture and low molecular weight substances, a twin-shaft extruder with a vent hole is more preferably used. In addition, from the viewpoint of improving the kneading strength and making the uniform dispersibility of the plasticizer good, a twin-shaft extruder with a screw having a kneading disk portion is preferably used. The temperature of the preparation process depends on the melting point of the PMP and the decomposition temperature of the plasticizer, but is preferably 220 to 300°C, more preferably 240 to 290°C.

[0093] The resin composition obtained in the preparation process can be temporarily granulated, melted again and used for melt film, or can be directly introduced into a spinneret for melt film. When temporarily granulated, it is preferred to use a resin composition in which the particles are dried and the moisture content is below 200ppm (mass basis). By making the moisture content below 200ppm (mass basis), the deterioration of the resin can be suppressed.

[0094] (Forming process)

[0095] In the separation membrane forming step, a molten mixture of PMP and plasticizer, namely a resin composition, is discharged from a discharge spinneret, passes through an air run section, and then introduced into a cooling bath to thermally induce phase separation of the resin composition, which is then wound to obtain a separation membrane.

[0096] Hereinafter, the case where the separation membrane is a hollow fiber membrane is described. As a specific method, the resin composition obtained in the preparation process in a molten state is discharged from the tube on the outside of the double annular nozzle for spinning, and the hollow portion forming gas is discharged from the tube on the inside of the double tubular spinneret. The temperature of the discharge portion (melt spinning kit) depends on the melting point of PMP and the decomposition temperature of the plasticizer, preferably 220 to 280°C, more preferably 230 to 270°C. At this time, it is important that the discharge gap of the discharge spinneret is 0.05 to 0.30 mm. The discharge gap mentioned here refers to the slit gap of the tube on the outside of the double tubular nozzle. It is speculated that by making the discharge gap of the discharge spinneret in this range, high shear is given to the resin composition in a molten state, thereby easily producing crystallization and promoting the formation of lamellar crystals. After the resin composition discharged in this way moves in the air (empty part), it is cooled and solidified in a cooling bath to obtain a separation membrane.

[0097] The discharge gap of the discharge spinneret is preferably 0.05 to 0.20 mm, particularly preferably 0.05 to 0.13 mm.

[0098] In addition, the resin composition discharged from the discharge spinneret is preferably exposed to a gaseous atmosphere that promotes the evaporation of the plasticizer, i.e., an atmosphere that can cause the evaporation of the plasticizer, before being introduced into a cooling bath. The gas used for the formation of the gaseous atmosphere is not particularly limited, and air or nitrogen is preferably used. The gaseous atmosphere usually has a temperature lower than the discharge spinneret temperature.

[0099] It is important to allow the resin composition discharged from the discharge spinneret to pass through a 30-80 mm empty run section and then be introduced into a cooling bath. Through the 30-80 mm empty run section, crystallization becomes easy to proceed, the formation of layered crystals is promoted, and the stability of spinning becomes good. It should be noted that the empty run section referred to here refers to the space from the spinneret plane of the discharge spinneret to the solvent plane of the cooling bath. It should be noted that sometimes the "distance from the spinneret plane to the solvent plane" is referred to as the "empty run distance".

[0100] The air travel distance is preferably 30 to 70 mm, more preferably 35 to 60 mm, and particularly preferably 40 to 50 mm.

[0101] Here, a cooling bath for cooling the resin composition discharged from the discharge spinneret will be described.

[0102] The temperature of the cooling bath depends on the type of solvent used in the cooling bath, but is preferably 5 to 45°C, more preferably 10 to 40°C.

[0103] The solvent of the cooling bath is preferably selected based on the affinity with the PMP and the plasticizer. As the solvent of the cooling bath, it is preferred to use a solvent whose solubility parameter distance Ra relative to the PMP is in the range of 5 to 13 and whose solubility parameter distance Rb relative to the plasticizer is in the range of 4 to 10. More preferably, a solvent whose Ra is in the range of 10 to 12 and whose Rb is in the range of 4 to 6 is used for the cooling bath. By having Ra and Rb in the aforementioned range, the dense layer can be thinned and the permeability can be improved.

[0104] The affinity of PMP to the solvent of the cooling bath can be calculated by three-dimensional Hansen solubility parameters as described in the literature (Ind. Eng. Chem. Res. 2011, 50, 3798-3817). Specifically, the smaller the solubility parameter distance (Ra) of the following formula (1), the higher the affinity of PMP to the solvent.

[0105] [Number 1]

[0106]

[0107] Here, δ Ad ,δ Ap and δ Ah are the dispersion term, polar term and hydrogen bond term of the solubility parameter of PMP, δ Cd ,δ Cp and δ Ch They are the dispersion term, polar term and hydrogen bonding term of the solvent solubility parameter respectively.

[0108] The affinity of the plasticizer to the solvent of the cooling bath can also be estimated in the same manner. Specifically, the smaller the solubility parameter distance (Rb) in the following formula (2), the higher the affinity of the plasticizer to the solvent.

[0109] [Number 2]

[0110]

[0111] Here, δ Bd ,δ Bp and δ Bh is the dispersion term, polar term and hydrogen bond term of the solubility parameter of PMP, δ Cd ,δ Cp and δ Ch are the dispersion term, polar term and hydrogen bonding term of the solubility parameter of the solvent.

[0112] When the solvent is a mixed solvent, the solubility parameter (δ Mixture ) can be obtained by the following formula (3).

[0113] [Number 3]

[0114] δMixture =∑Φ i δ i Formula (3)

[0115] Here, δ i is the volume fraction and solubility parameter of component i, and is valid for each of the dispersion term, polar term and hydrogen bond term. Here, "volume fraction of component i" refers to the ratio of the volume of component i before mixing to the sum of the volumes of all components before mixing. The three-dimensional Hansen solubility parameter of the solvent is used when it is recorded in the literature (Ind. Eng. Chem. Res. 2011, 50, 3798-3817.). For unrecorded solvent parameters, the values ​​included in the software "Hansen Solubility Parameter in Practice" developed by Charls Hansen et al. are used. The three-dimensional Hansen solubility parameters of solvents and polymers that are not recorded in the above software can be calculated by using the Hansen sphere method of the above software.

[0116] In the method for producing a separation membrane of the present invention, when dibutyl phthalate is used as a plasticizer, the solvent used in the cooling bath of the forming step is preferably: mono(2-ethylhexyl) phthalate, di(tridecyl) phthalate, diisodecyl phthalate, benzyl butyl phthalate, triacetin, ascorbyl palmitate, sorbitan monooleate, propylene glycol monostearate, methyl isoamyl ketone, methyl ethyl Ketone, propylene glycol methyl ether acetate, N, N-dimethylacetamide, methyl isobutyl ketone, methyl oleate, methyl propyl ketone, methyl acetate, tributyl phosphate, N-methylpyrrolidone, tetrahydrofuran, 1-nitropropane, propyl propionate, butyl propionate, butyl glycol acetate, diisobutyl ketone, cyclopentyl methyl ether, amyl acetate, acetone, ethyl acetate, dimethyl isosorbide, 1,4-dioxane, 1,3-dioxane, ethylene glycol 2-ethylhexyl ether, etc. Among them, Ra and Rb of the solvent selected from benzyl butyl phthalate, methyl ethyl ketone, N-methylpyrrolidone, 1-nitropropane and acetone are preferably within the above-mentioned preferred ranges.

[0117] In the forming process, the separation membrane solidified in the cooling bath is wound by a winding device. At this time, the value of the draft ratio calculated based on the (winding speed) / (discharge speed from the discharge spinneret) of the winding device is preferably 1 to 10. The value of the draft ratio is more preferably 1 to 8. By having a draft ratio of 1 or more, the winding is stable and the variation in the shape of the separation membrane becomes smaller. By setting the draft ratio to 10 or less, excessive stretching of the resin composition discharged from the spinneret can be suppressed, and leakage caused by defects in the dense layer can be suppressed.

[0118] (Cleaning process)

[0119] By dipping the resin combination thus obtained in a solvent that does not dissolve polymer but can be mixed with a plasticizer, the porosity of the separation membrane can be improved by the cleaning process through which the plasticizer is dissolved from the separation membrane. At this time, by using a solvent or a mixed solvent with appropriate affinity for the plasticizer, a good solvent exchange can be carried out to improve cleaning efficiency. As the solvent used in the cleaning process, as long as it is a solvent that does not dissolve the separation membrane and can be mixed with a plasticizer, it is not particularly limited. As a specific example, methanol, ethanol, isopropanol, acetone, etc. are preferably used.

[0120] (Residual plasticizer)

[0121] The amount of the plasticizer remaining after the washing step is preferably as small as possible. Specifically, the amount of the plasticizer remaining in the resin composition constituting the separation membrane is preferably 1,000 ppm or less, more preferably 500 ppm or less, and even more preferably 100 ppm or less.

[0122] (Drying process)

[0123] In order to remove the attached solvent in the washing step, the resin composition after the washing step is preferably subjected to a drying step. The drying temperature is preferably a temperature at which the solvent that does not dissolve the polymer but is miscible with the plasticizer can be vaporized and removed, and specifically preferably room temperature to 150°C.

[0124] In this way, the separation membrane of the present invention containing PMP as a main component can be produced.

[0125] (Component)

[0126] The separation membrane of the present invention obtained as described above can be filled in a housing by a conventionally known method to form an assembly. For example, a hollow fiber membrane assembly has a plurality of hollow fiber membranes and a cylindrical housing. After a plurality of hollow fiber membranes are bundled and filled in a cylindrical housing, a thermosetting resin such as polyurethane or epoxy resin is used to fix the end thereof to the above-mentioned housing and seal it. After the thermosetting resin is cured, the opening surface of the hollow fiber membrane is obtained by cutting off the end of the hollow fiber membrane, thereby obtaining an assembly.

[0127] The separation membrane of the present invention can be suitably used for separating gas from liquid or imparting gas to liquid. For example, it can be preferably used as a degassing membrane for a degassing membrane module for reducing the amount of dissolved gas in a solution in a semiconductor manufacturing line or the like.

[0128] The degassing membrane module comprises a housing and the separation membrane of the present invention, wherein the separation membrane is filled in the housing. It should be noted that the liquid to be treated in the "degassing membrane module" of the present invention is water, an organic solvent, and a mixture thereof, but blood is not a target.

[0129] Example

[0130] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to these Examples.

[0131] [Measurement and evaluation methods]

[0132] The respective property values ​​in the examples were obtained by the following methods.

[0133] (1) Outer and inner diameters of hollow fiber membranes (μm)

[0134] After the hollow fiber membrane is frozen with liquid nitrogen, stress is applied (using a razor or a slicer as needed) to cut it so that the diameter section of the hollow fiber membrane is exposed. The exposed diameter section is observed using an optical microscope, and the average values ​​of the outer diameter and inner diameter of 10 randomly selected points are respectively set as the outer diameter and inner diameter of the hollow fiber membrane.

[0135] (2) Hollowness ratio of hollow fiber membrane (%)

[0136] The hollowness of the hollow fiber membrane was calculated by the following formula from the outer diameter and inner diameter obtained in the above (1).

[0137] Hollowness (%) = 100 × [Inner diameter (μm 2 )] 2 / [Outer diameter (μm 2 )] 2 .

[0138] (3) Breathability (GPU)

[0139] A small module with an effective length of 100 mm including three hollow fiber membranes is prepared. Specifically, three hollow fiber membranes are bundled and inserted into a plastic tube as a cylindrical shell, and then a thermosetting resin is injected into the gaps between the hollow fiber membranes and the gaps between the hollow fibers and the tube at the ends of the hollow fiber membrane bundle, and the resin is cured to seal. The open surface of the hollow fiber membrane is obtained by cutting the ends of the sealed hollow fiber membranes, thereby preparing a small module for evaluation. Using this small module, carbon dioxide and nitrogen are used separately as measuring gases for evaluation, and the pressure change on the permeation side of carbon dioxide or nitrogen per unit time is measured by an external pressure method at a measuring temperature of 37°C. Here, the pressure difference between the supply side and the permeation side is set to 100 kPa.

[0140] Next, the permeation flow rates Q calculated for carbon dioxide and nitrogen by the following formulae are referred to as CO2 permeation performance and N2 permeation performance, respectively. Here, the membrane area is calculated from the outer diameter and length of the hollow fiber membrane in the region contributing to gas permeation.

[0141] Throughput Q(GPU) = 10 -6 [Gas permeation volume (cm 3 )] / [Membrane area (cm 2 )×time (s)×pressure difference (cmHg)].

[0142] The ratio Q(CO2) / Q(N2) of the CO2 permeability Q(CO2) and the N2 permeability Q(CO2) measured as described above is defined as the gas separation coefficient α(CO2 / N2).

[0143] Furthermore, the N2 permeability measured as described above was defined as X, and the N2 permeability at a differential pressure of 100 kPa measured in the same manner after immersing the same hollow fiber membrane in chloroform for 5 seconds was defined as Y, and the N2 permeability change rate Y / X was measured.

[0144] (4) Thickness of dense layer (μm)

[0145] After freezing the separation membrane with liquid nitrogen in the same manner as in (1) above, stress is applied (using a razor, a microtome, or a broad ion beam as required) to cut the membrane so that a radial section or a longitudinal section is exposed. Next, the exposed section is sputtered with platinum under the following conditions and observed using a SEM at a magnification of 10,000 times.

[0146] The obtained image was binarized using the image analysis software "ImageJ". The binarization was performed as follows, that is, when the horizontal axis represents the brightness in the analysis image and the vertical axis represents the number of pixels at the corresponding brightness, when the number of pixels at the brightness with the largest number of pixels is set to A, the point with the smaller brightness of the two points with the brightness of 1 / 2A is set as the threshold value. Furthermore, for the obtained binarized image, noise removal (equivalent to Despeckle in ImageJ) was performed once to replace all pixels with the central value of 3×3 pixels near the pixel, and the obtained image was used as the analysis image. A cross section cut along the thickness direction of the separation membrane was photographed with an SEM at a magnification of 10,000 times, and an example of the obtained image is shown in Figure 1 ,Will Figure 1 The image is de-noised and binarized. Figure 2 Next, the pores were extracted using the Analyze Particles command of ImageJ. When a straight line perpendicular to the outer surface was drawn from any point on the outer surface of the separation membrane to the inner surface, the length until the first hole with a diameter exceeding 10 nm was reached was set as the dense layer thickness. It should be noted that the measurement was performed at any 10 points, and the average value was used as the dense layer thickness. Figure 2 The image showing the contours of voids larger than 10 nm and the image showing the thickness of the dense layer is shown in Figure 3 .

[0147] (Sputtering)

[0148] Device: Made by Hitachi High-Technology Co., Ltd. (E-1010)

[0149] Evaporation time: 40 seconds

[0150] Current value: 20mA

[0151] (SEM)

[0152] Device: Made by Hitachi High-Technology Co., Ltd. (SU1510)

[0153] Accelerating voltage: 5kV

[0154] Probe current: 30.

[0155] (5) Number of voids larger than 10 μm in the support layer

[0156] After freezing the separation membrane with liquid nitrogen in the same manner as in (1) above, stress is applied (using a razor, a microtome, or a wide ion beam as needed) to cut the membrane so that the radial section or the longitudinal section is exposed. Then, the exposed section is sputtered with platinum under the following conditions and observed using a SEM at a magnification of 2,000 times. In the observed section, holes with a diameter greater than 10 μm, i.e., holes with an area greater than 78.5 μm, are removed from each field of view. 2 All the holes are extracted and their number is calculated. It should be noted that the diameters of the holes at the ends of the image that are not in the field of view as a whole are also calculated in this state. The extraction of holes is performed after binarizing the analysis image in the image analysis software "ImageJ" (Huang's binarization). Furthermore, for the obtained binarized image, noise removal is performed once to replace all pixels with the central value of 3×3 pixels near the pixel (equivalent to Despeckle in ImageJ), and the obtained image is used as the analysis image. The extraction of holes is performed using the Analyze Particles command of ImageJ, and the number of holes obtained is calculated. It should be noted that the measurement is performed on any 5 locations, and the average value is used as the number of voids larger than 10μm in the support layer.

[0157] (Sputtering)

[0158] Device: Made by Hitachi High-Technology Co., Ltd. (E-1010)

[0159] Evaporation time: 40 seconds

[0160] Current value: 20mA

[0161] (SEM)

[0162] Device: Made by Hitachi High-Technology Co., Ltd. (SU1510)

[0163] Accelerating voltage: 5kV

[0164] Probe current: 30.

[0165] (6) Average pore size of the support layer (nm)

[0166] After freezing the separation membrane with liquid nitrogen in the same manner as in (1) above, stress is applied (using a razor, microtome, or wide ion beam as needed) to cut it so that the radial section or longitudinal section is exposed. Next, the exposed section is sputtered with platinum under the following conditions. When the section is observed using an SEM at a magnification of 2,000 times, all holes with a diameter greater than 10 nm in each field of view are extracted, and their respective diameters and the number of holes are calculated. Then, the total of all diameters is divided by the number of holes to calculate the average pore size per field of view. It should be noted that the diameter and number of holes at the ends of the image that do not enter the field of view as a whole are also calculated in this state. The extraction of holes is performed after binarizing the analysis image (Huang's binarization) in the image analysis software "ImageJ". Furthermore, for the resulting binarized image, noise removal (equivalent to Despeckle in ImageJ) is performed once to replace all pixels with the central value of 3×3 pixels near the pixel, and the resulting image is used as the analysis image. The pores were extracted using the Analyze Particles command of ImageJ, and the number of the obtained pores was calculated. It should be noted that the measurement was performed at 5 random locations, and the average value was used as the average pore diameter of the support layer.

[0167] (Sputtering)

[0168] Device: Made by Hitachi High-Technology Co., Ltd. (E-1010)

[0169] Evaporation time: 40 seconds

[0170] Current value: 20mA

[0171] (SEM)

[0172] Device: Made by Hitachi High-Technology Co., Ltd. (SU1510)

[0173] Accelerating voltage: 5kV

[0174] Probe current: 30.

[0175] (7) Void ratio (%)

[0176] The fiber length L (mm) and mass M (g) of the hollow fiber membrane vacuum dried at 25°C for 8 hours were measured. The density ρ1 of the hollow fiber membrane was calculated by the following formula using the values ​​of the outer diameter (mm) and inner diameter (mm) measured in (1) above.

[0177] ρ1=M / [π×{(outer diameter / 2) 2 -(inner diameter / 2) 2}×L]

[0178] In addition, the porosity ε (%) was calculated by the following formula.

[0179] ε=1-ρ1 / ρ2

[0180] Here, ρ2 is the density of the polymer constituting the hollow fiber membrane.

[0181] (8) Area ratio of layered crystals

[0182] After sputtering the surface of the separation membrane on the dense layer side with platinum under the following conditions, it was observed using SEM at a magnification of 60,000 times. The bright part of the SEM image is layered crystals. The layered crystals, that is, the bright part of the SEM image, are extracted from the observed image, and the ratio of the area of ​​the layered crystals to the area of ​​the entire observed image is calculated as the area ratio of the layered crystals in the surface on the dense layer side. The extraction of layered crystals is performed after binarizing the observed image (Otsu's binarization) in the image analysis software "ImageJ". For the obtained binarized image, noise removal (equivalent to Despeckle in ImageJ) is performed 5 times to replace all pixels with the central value of 3×3 pixels near the pixel, and the obtained image is used as an analysis image. The extraction of layered crystals is performed using the Analyze Particles command of ImageJ, all the obtained bright parts are extracted, and the area ratio occupied by the layered crystals is calculated from the area of ​​the obtained bright parts. It should be noted that the measurement is performed on any 5 places, and the average value is used as the area ratio occupied by the layered crystals.

[0183] (Sputtering)

[0184] Device: Made by Hitachi High-Technology Co., Ltd. (E-1010)

[0185] Evaporation time: 40 seconds

[0186] Current value: 20mA

[0187] (SEM)

[0188] Device: Made by Hitachi High-Technology Co., Ltd. (S5500)

[0189] Accelerating voltage: 5kV

[0190] Probe current: 30.

[0191] (9) Method for calculating the period of layered crystals using SEM images

[0192] The surface of the separation membrane having the dense layer was sputtered with platinum under the same conditions as in (8), and then observed using a SEM at a magnification of 60,000 times. The calculation was performed using the image processing software ImageJ according to the following method.

[0193] A. SEM images were imported into ImageJ (file size was set to 512 × 512 pixels).

[0194] B. When executing Process / FFT / FD Math, the autocorrelation function is used as the Result output image, so the image type is set to 16 bit.

[0195] C. Use the line tool to draw a horizontal line through the bright point in the center of the image.

[0196] D. Execute Analyze / Plot Profile and output the result points (Plot of Result).

[0197] E. Press the List button to output the intensity and distance and create a graph.

[0198] F. The distance from the high-brightness point in the center of the image of the autocorrelation function (output image) to the first proximal peak is measured to calculate the period of the layered crystal.

[0199] (10) Surface crystallinity

[0200] The surface of the hollow fiber membrane that had been vacuum dried at 25°C for 8 hours was subjected to ATR spectrum measurement using an FTIR (FTS-55A) manufactured by BioRad DIGILAB equipped with a single reflection ATR accessory. It should be noted that ATR crystallization was performed using a diamond prism with an incident angle of 45° and 64 accumulations. Based on the obtained ATR spectrum, the crystallinity was calculated using the intensity ratio of the specified bands corresponding to the components constituting the hollow fiber membrane. In the case of a hollow fiber membrane with PMP as the main component, 849 cm -1 The intensity of the band near 1169 cm -1 The surface crystallinity was calculated from the intensity of the band near the surface using the following formula.

[0201] IR intensity ratio of the outer surface = [849cm -1 Band intensity near] / [1169cm -1Band intensity near

[0202] Crystallinity (%) = 172.9 × IR intensity ratio of the outer surface.

[0203] (11) The presence or absence of orientation of layered crystals and the orientation direction of layered crystals

[0204] After sputtering the surface of the hollow fiber membrane with a dense layer on one side with platinum under the following conditions, an SEM was used to photograph at a magnification of 60,000 times in such a way that the length direction of the hollow fiber membrane became a horizontal direction. The obtained SEM image was cut into 512×512 pixels, and after Fourier transform, the horizontal direction was set to 0°, and the scanning was performed sequentially in the range of -90° to 90° from the center point of the Fourier transform image by the following method. Specifically, in one scan, a range of 50 pixels and 4° in length from the center point of the Fourier transform image was scanned, and the average intensity of the range was calculated. This operation was performed every 4° from -90° to 90°, thereby making a graph in which the scanning angle was plotted on the axis and each average intensity was plotted on the vertical axis. The value obtained by adding 90° to the angle showing the maximum value in the figure is set as the orientation direction of the layered crystal.

[0205] It should be noted that the specific analysis method using ImageJ is as follows. Shooting is performed at a magnification of 60,000 times, and the obtained SEM image is cut out to 512 × 512 pixels, and Fourier transform is implemented. In the Radial Profile Angle in ImageJ, the X center (X center) and the Y center (Y center) are respectively set to 256 pixels, the radius (Radius) is set to 50 pixels, and the integration angle (Integration Angle) is set to 2 ° to measure the Fourier transform image thus obtained, and the starting angle (Starting Angle) is set to -88 ° to 88 ° and implemented every 4 ° to obtain the average intensity at each angle. By plotting the obtained data, a graph of the horizontal axis angle and the vertical axis average intensity can be prepared.

[0206] The presence or absence of orientation of the layered crystals is confirmed by the following method. In a graph obtained by plotting the angle on the horizontal axis and the average intensity on the vertical axis, when the minimum value and the maximum value do not differ by more than 5%, that is, when the value of 100×(MAX-MIN) / MAX when the maximum value is MAX and the minimum value is MIN is less than 5, the layered crystals are considered to be non-oriented.

[0207] (Sputtering)

[0208] Device: Made by Hitachi High-Technology Co., Ltd. (E-1010)

[0209] Evaporation time: 40 seconds

[0210] Current value: 20mA

[0211] (SEM)

[0212] Device: Made by Hitachi High-Technology Co., Ltd. (S5500)

[0213] Accelerating voltage: 5kV

[0214] Probe current: 30.

[0215] [PMP]

[0216] As PMP, the following materials were prepared.

[0217] PMP: TPX (registered trademark) DX845 (density: 833kg / m 3 , MFR: 9.0g / 10min).

[0218] [Other raw materials]

[0219] Plasticizer: dibutyl phthalate.

[0220] (Example 1)

[0221] PMP35 mass% and 65 mass% of dibutyl phthalate as a plasticizer were supplied to a twin-screw extruder, melt-kneaded at 290°C, and then introduced into a melt spinning kit with a spinning temperature set to 245°C, and spun downward from the outer annular portion of the discharge spinneret having one spinneret hole (double circular tube type, discharge aperture 2.0mm, discharge gap 0.10mm). At this time, the hollow portion forming gas is air discharged from the inner tube of the double tubular spinneret in the form of an accompanying airflow. After the spun hollow fiber passes through the air-running portion, it is introduced into a cooling bath using triacetin as a solvent and wound with a winding machine in a draft ratio of 8. At this time, the air-running distance is set to 60mm. Here, a metal filter with a diameter of 200μm is used as a filter in the melt spinning kit. The wound hollow fiber is immersed in isopropanol for 24 hours for cleaning, and then vacuum dried at room temperature to remove isopropanol to obtain a hollow fiber membrane. The physical properties of the obtained hollow fiber membrane are shown in Table 1. The area ratio of lamellar crystals in the surface (1) of the dense layer side of the obtained hollow fiber membrane was 42.3%, the porosity was 55%, the N2 permeability was 42GPU, the N2 permeability change rate Y / X before and after chloroform immersion was 0.81, and the gas separation coefficient α (CO2 / N2) was 4.9, which showed excellent permeability and high resistance to organic solvents.

[0222] (Example 2)

[0223] A hollow fiber membrane was obtained in the same manner as in Example 1 except that the air-passing distance was set to 45 mm. As a result, as shown in Table 1, the area ratio of lamellar crystals in the surface (1) on the side having the dense layer of the obtained hollow fiber membrane was 38.7%, the N2 permeability X was 60 GPU, and the N2 permeability change rate Y / X before and after chloroform immersion was 0.78.

[0224] (Example 3)

[0225] A hollow fiber membrane was obtained in the same manner as in Example 1 except that the air-passing distance was set to 40 mm. As a result, as shown in Table 1, the area ratio of lamellar crystals in the surface (1) on the side having the dense layer of the obtained hollow fiber membrane was 30.8%, the N2 permeability X was 68 GPU, and the N2 permeability change rate Y / X before and after chloroform immersion was 0.75.

[0226] (Example 4)

[0227] A hollow fiber membrane was obtained in the same manner as in Example 1 except that the air distance was set to 35 mm. As a result, as shown in Table 1, the area ratio of lamellar crystals on the surface (1) of the dense layer side of the obtained hollow fiber membrane was 28.7%, and the N2 permeation performance change rate Y / X before and after chloroform immersion was 0.63.

[0228] (Example 5)

[0229] A hollow fiber membrane was obtained in the same manner as in Example 1 except that the discharge gap was set to 0.15 mm and the air distance was set to 45 mm. As a result, as shown in Table 1, the area ratio of the lamellar crystals on the surface (1) of the dense layer side of the obtained hollow fiber membrane was 27.3%, and the N2 permeation performance change rate Y / X before and after chloroform immersion was 0.57.

[0230] (Example 6)

[0231] A hollow fiber membrane was obtained in the same manner as in Example 5 except that the air distance was set to 35 mm. As a result, as shown in Table 1, the area ratio of lamellar crystals on the surface (1) of the dense layer side of the obtained hollow fiber membrane was 24.7%, and the N2 permeation performance change rate Y / X before and after chloroform immersion was 0.46.

[0232] (Example 7)

[0233] A hollow fiber membrane was obtained in the same manner as in Example 5 except that the air distance was set to 30 mm. As a result, as shown in Table 1, the area ratio of lamellar crystals on the surface (1) of the obtained hollow fiber membrane having a dense layer was 22.9%, and the N2 permeation performance change rate Y / X before and after chloroform immersion was 0.44.

[0234] (Example 8)

[0235] The same procedure as in Example 1 was followed except that the coagulation bath was N-methylpyrrolidone and the air distance was 45 mm to obtain a hollow fiber membrane. As shown in Table 1, the area ratio of lamellar crystals on the surface (1) of the obtained hollow fiber membrane having a dense layer was 34.9%, and the N2 permeability change rate Y / X before and after chloroform immersion was 0.78. Furthermore, the thickness of the dense layer was 0.19 μm, and the N2 permeability was increased to 150 GPU by thinning the layer.

[0236] (Comparative Example 1)

[0237] A hollow fiber membrane was obtained in the same manner as in Example 1 except that the draft ratio was set to 231 and the discharge gap was set to 0.35 mm. As a result, as shown in Table 2, no lamellar crystals were observed on the surface (1) on the dense layer side of the obtained hollow fiber membrane (i.e., the area ratio of the lamellar crystals was 0%), and the N2 permeation performance change rate Y / X before and after chloroform immersion showed a low value of 0.00.

[0238] (Comparative Example 2)

[0239] A hollow fiber membrane was obtained in the same manner as in Example 7 except that the discharge gap was set to 0.35 mm. As a result, as shown in Table 2, no lamellar crystals were observed on the surface (1) of the obtained hollow fiber membrane having the dense layer (i.e., the area ratio of the lamellar crystals was 0%), and the N2 permeation performance change rate Y / X before and after chloroform immersion showed a low value of 0.00.

[0240] (Comparative Example 3)

[0241] The spinning was performed in the same manner as in Example 1 except that PMP was set to 100 mass % and the draft ratio was set to 700, and the stretching temperature was set to 130°C and the stretching ratio was set to 2.3 times after air cooling, thereby obtaining a hollow fiber membrane. It should be noted that since there was no cooling bath, there was no air distance. As a result, as shown in Table 2, the porosity of the obtained hollow fiber membrane was 20%, and the N2 permeability showed a low value of 3GPU. The lamellar crystal ratio was very low at 1%, and the period could not be calculated.

[0242] (Example 9)

[0243] A hollow fiber membrane was obtained in the same manner as in Example 1 except that the air-passing distance was set to 75 mm. As a result, as shown in Table 2, the area ratio of lamellar crystals in the surface (1) on the side having the dense layer of the obtained hollow fiber membrane was 46.7%, the N2 permeability X was 33 GPU, and the N2 permeability change rate Y / X before and after chloroform immersion was 0.90.

[0244] (Example 10)

[0245] A hollow fiber membrane was obtained in the same manner as in Example 1 except that the discharge gap was set to 0.20 mm and the air distance was set to 30 mm. As a result, as shown in Table 2, the area ratio of lamellar crystals on the surface (1) of the dense layer side of the obtained hollow fiber membrane was 16.8%, and the N2 permeation performance change rate Y / X before and after chloroform immersion was 0.31.

[0246] (Example 11)

[0247] A hollow fiber membrane was obtained in the same manner as in Example 8 except that the air distance was set to 30 mm. As a result, as shown in Table 2, the area ratio of lamellar crystals in the surface (1) on the side having the dense layer of the obtained hollow fiber membrane was 28.1%, the N2 permeability X was 183 GPU, and the N2 permeability change rate Y / X before and after chloroform immersion was 0.49.

[0248] [Table 1]

[0249]

[0250] [Table 2]

[0251]

[0252] The separation membranes obtained in Examples 1 to 11 have an area ratio of lamellar crystals on the surface (1) on the dense layer side that satisfies the requirements of the present invention, and all have high solvent resistance with a N2 permeability change rate Y / X before and after chloroform immersion being 0.3 or more. On the other hand, the separation membranes of Comparative Examples 1 to 3, in which the area ratio of lamellar crystals on the surface (1) on the dense layer side is low, all show low values ​​for the N2 permeability change rate Y / X before and after chloroform immersion.

[0253] In addition, in any of Examples 1 to 11, the number of voids larger than 10 μm in the support layer was zero.

[0254] Industrial Applicability

[0255] The separation membrane of the present invention can be suitably used for separating gas from liquid or imparting gas to liquid. For example, in semiconductor production lines, liquid crystal color filter production lines, and inkjet printer ink manufacturing, it can be suitably used as a degassing membrane for reducing the amount of dissolved gas in water, aqueous solutions, organic solvents, and resist liquids, or as a gas exchange membrane in an artificial lung for medical purposes. In particular, as a degassing membrane, it is very useful in the degassing purposes of photoresist liquid and developer used in the photolithography of semiconductor production lines.

[0256] Explanation of symbols

[0257] 1. Membrane surface

[0258] 2 Thickness of dense layer

[0259] 3. Length direction of separation membrane

Claims

1. A separation membrane comprising poly(4-methyl-1-pentene) as a main component and having a dense layer in at least one surface layer, wherein the area ratio of lamellar crystals in the surface (1) having the dense layer is 5 to 50%.

2. The separation membrane according to claim 1, which has a porosity of 30 to 70%.

3. The separation membrane according to claim 1 or 2, wherein The crystallinity of the surface (1) is 5 to 30%.

4. The separation membrane according to any one of claims 1 to 3, wherein The period of the layered crystals in the surface (1) is 10 to 80 nm.

5. The separation membrane according to any one of claims 1 to 4, wherein The layered crystals in the surface (1) have orientation.

6. The separation membrane according to any one of claims 1 to 5, wherein The orientation direction of the lamellar crystals on the surface (1) is 60 to 120° relative to the longitudinal direction of the separation membrane.

7. The separation membrane according to any one of claims 1 to 6, wherein The thickness of the dense layer is 0.1-0.8 μm.

8. The separation membrane according to any one of claims 1 to 7, wherein The separation membrane is in the shape of a hollow fiber.

9. The separation membrane according to claim 8, wherein The surface (1) is the outer surface of the separation membrane in the shape of a hollow fiber. 10 . The separation membrane according to claim 1 , which is a gas permeable membrane, and the gas permeable membrane can be suitably used for separating gas from liquid or for adding gas to liquid. 11 . The separation membrane according to claim 1 , wherein a gas separation coefficient α (CO 2 / N 2 ) is 1 or more. 12 . The separation membrane according to claim 1 , which has a N 2 permeability of 5 GPU or more at a differential pressure of 100 kPa.

13. A separation membrane comprising poly(4-methyl-1-pentene) as a main component, wherein: At least one surface layer has a dense layer, When the N2 permeability of the separation membrane at a differential pressure of 100 kPa is X, and the N2 permeability of the separation membrane at a differential pressure of 100 kPa after immersing the separation membrane in chloroform for 5 seconds is Y, The value of the N2 permeability change rate Y / X is 0.30 to 1.

20. 14 . A degassing membrane module comprising a housing and the separation membrane according to claim 1 , wherein the housing is filled with the separation membrane.

15. A method for producing a separation membrane, comprising the steps (1) to (2) below: (1) a preparation step of melt-kneading a mixture containing 10 to 50% by mass of poly(4-methyl-1-pentene) and 50 to 90% by mass of a plasticizer to obtain a resin composition; (2) A molding step of discharging the resin composition from a discharge spinneret having a gap of 0.05 to 0.3 mm, introducing the resin composition into a cooling bath through an air path having a distance of 30 to 80 mm from the spinneret plane to the solvent plane, and then winding the composition to obtain a resin molded product.

16. The method for producing a separation membrane according to claim 15, characterized in that: In the molding step, a solvent having a solubility parameter distance Ra of 5 to 13 with respect to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 4 to 10 with respect to the plasticizer is used in the cooling bath.

Citation Information

Patent Citations

  • Manufacture of hollow fiber dual membrane

    JP1995116483A

  • Method for manufacturing monolithic asymmetric polyolefin membrane

    JP2002535114A